Enabling tax bargaining: Supporting more meaningful tax transparency and taxpayer engagement in Ghana and Sierra Leone. (19th July 2021) - van den Boogaard, Vanessa; Prichard, Wilson; Beach, Rachel; Mohiuddin, Fariya
Abstract: Motivation: While there is increasing evidence that taxation can contribute to greater government responsiveness and accountability, such positive outcomes are not guaranteed. If the environment does not enable tax bargaining, there is a risk that taxation will amount to little more than enforced extraction. Purpose: We consider how such enabling environments may be fostered and identify specific strategies that governments, civil society actors, and donors can adopt to strengthen the links between taxation, responsiveness, and accountability. Methods and approach: We undertake two case studies of tax transparency and taxpayer engagement in Ghana and Sierra Leone, making use of data from taxpayer surveys, focus group discussions (FGDs), and interviews with key stakeholders in government, civil society, and donor agencies. Findings: We highlight two key findings. First, meaningful transparency requires that information is comprehensive, relates to taxpayers' priorities, and serve as a basis for dialogue between taxpayers and governments. Second, there is a need to proactively encourage taxpayer engagement by supporting forums for engagement that taxpayers perceive as safe, secure and sincere. This has been most successful where governments have visibly demonstrated responsiveness to citizens' concerns, even on a small scale, while partnering with civil society to foster trust and dialogue. Policy implications: Our findings point to the need for taxpayer education and engagement programmes that make information more accessible and more directly relevant to taxpayers' everyday experiences. In particular, policymakers and development partners need to expand existing efforts to facilitate engagement and dialogue regarding what revenues are collected and how they are spent. We highlight the valuable role that civil society can play as translators of tax information, enablers of public forums, and trainers to support greater tax literacy and sustained taxpayer engagement.